2014
DOI: 10.3402/tdp.v2.24663
|View full text |Cite|
|
Sign up to set email alerts
|

Genetics of antipsychotic drug outcome and implications for the clinician: into the limelight

Abstract: Background and purpose: Antipsychotics (APs) are the primary method of treatment for schizophrenia and other psychotic disorders. Unfortunately, lengthy trial-and-error approaches are typically required to find the optimal medication and dosage due to a large interindividual variability with outcome to AP treatment. The literature has shown abundant evidence for a genetic component in individuals' responses to APs. Pharmacogenetic studies analyze specific genetic markers and their association with symptom impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 99 publications
0
5
0
Order By: Relevance
“…To date, many candidate gene-based association studies and genome-wide association studies (GWAS) have sought to identify genetic variants associated with psychotropic treatment response and these are discussed next. (Changasi et al, 2014;Fabbri and Serretti, 2015;Porcelli et al, 2011). Variations within the drug metabolizing gene CYP2D6 have been most extensively investigated in terms of pharmacokinetics of psychotropic medication (Porcelli et al, 2011).…”
Section: Moving To Precision Medicine In Psychiatrymentioning
confidence: 99%
“…To date, many candidate gene-based association studies and genome-wide association studies (GWAS) have sought to identify genetic variants associated with psychotropic treatment response and these are discussed next. (Changasi et al, 2014;Fabbri and Serretti, 2015;Porcelli et al, 2011). Variations within the drug metabolizing gene CYP2D6 have been most extensively investigated in terms of pharmacokinetics of psychotropic medication (Porcelli et al, 2011).…”
Section: Moving To Precision Medicine In Psychiatrymentioning
confidence: 99%
“…We selected genes shown to be associated with antipsychotic drug response from pharmacodynamic candidate gene studies and genome-wide association studies. eTable 2 in Supplement 2 lists the most promising candidate genes, as reviewed by Changasi et al, and the genes shown to be associated with drug response from the 2 published genome-wide association studies …”
Section: Methodsmentioning
confidence: 99%
“…In studies on clozapine, it was possible to identify single-nucleotide variants (SNVs) in the human leukocyte antigen (HLA)—the 6672G/C nucleotide variant, which is being tried to be used as a marker of the effectiveness of schizophrenia. The test had a high specificity; however, it was obsolete for commercial use due to low market interest [ 11 ]. Similarly, on daily basis practice, the testing of polymorphisms in CYP2D6 with regard to the metabolism of clozapine and determining its effective dose is used [ 12 ].…”
Section: Introductionmentioning
confidence: 99%